Ritual Hada O Na’adi dalam Pesta Adat Pernikahan di Mali Hada O Na'adi Rituals at a Traditional Marriage Party in Mali - Christin Ekaristi Molana (Universitas Negeri Medan, 2021)
This research relates to one of the cultures that exist in Mali, namely the culture of eating indigenous. The culture of traditional eating is known as the ritual of hada o na'adi, this ritual is only carried out in a traditional wedding party and is a legacy from ancestors that is still preserved to this day. This paper also aims to look at the hada o na'adi ritual function in a traditional wedding party in Mali. The method used is a qualitative research method using direct interview techniques with several people representing each tribe in Mali and literature study to strengthen this writing. based on data obtained from the field, this study explains that the ritual of hada o na'adi has two main functions, namely the religious function and social function. The religious function of the hada o na'adi ritual is to have magical power to better organize people's mindsets and lives, while the social function is as a symbol of togetherness, courtesy, mutual respect and order.